microRNA‐143‐3p attenuated development of hepatic fibrosis in autoimmune hepatitis through regulation of TAK1 phosphorylation - Tu, Hanxiao (J Cell Mol Med, 2019)
Autoimmune hepatitis (AIH) is a chronic liver disease due to autoimmune system attacks hepatocytes and causes inflammation and fibrosis. Intracellular signalling and miRNA may play an important role in regulation of liver injury. This study aimed to investigate the potential roles of microRNA 143 in a murine AIH model and a hepatocyte injury model. Murine AIH model was induced by hepatic antigen S100, and hepatocyte injury model was induced by LPS. Mice and AML12 cells were separated into six groups with or without the treatment of miRNA‐143. Inflammation and fibrosis as well as gene expression were examined by different cellular and molecular techniques. The model was successfully established with the elevation of ALT and AST as well as inflammatory and fibrotic markers. Infection or transfection of mir‐143 in mice or hepatocytes significantly attenuated the development of alleviation of hepatocyte injury. Moreover, the study demonstrated phosphorylation of TAK1‐mediated miRNA‐143 regulation of hepatic inflammation and fibrosis as well as hepatocyte injury. Our studies demonstrated a significant role of miRNA‐143 in attenuation of liver injury in AIH mice and hepatocytes. miRNA‐143 regulates inflammation and fibrosis through its regulation of TAK1 phosphorylation, which warrants TAK1 as a target for the development of new therapeutic strategy of autoimmune hepatitis.